Plant-Parasitic Nematode Control in Horticultural Crops of Argentina - Salas, Augusto; Rusconi, José Matías; Eliceche, Daiana Pamela; Rosales, Matías Nicolás; Achinelly, María Fernanda; Chaves, Eliseo Jorge; Sauka, Diego Hernan (Springer, 2025)
The management of plant-parasitic nematodes has been traditionally carried out by using agrochemicals. However, conventional approaches often threaten the biodiversity and sustainability of the agroecosystem. Microorganisms, such as bacteria and fungi, offer an alternative to the traditional control of phytonematodes. Horticultural production is widespread throughout Argentina and does not escape crop pest problem. This chapter reviews the current state of conventional control of plant parasitic nematodes in Argentina, as well as the eco-friendly alternatives that have emerged in recent years. Aim is to provide a contribution for researchers around the world to combine efforts and agree on global paths for the control of organisms that are harmful to horticultural productions, globally. Microorganisms offer a beacon of hope for this purpose in the current situation.